Time-series analysis on relationship between short-term exposure to atmospheric ozone and the risk of non-accidental deaths in Hefei during 2017−2020 - Linling YU; Yu ZHU; Changchun XIAO (环境与职业医学, 2024)
BackgroundIn recent years, Hefei has experienced rapid industrial development, and the concentration of ozone (O3) in the environment has increased year by year. Ambient O3 pollution has become one of the big issues in Hefei.ObjectiveTo explore the health risks of non-accidental deaths (NAD) in local residents associated with ambient O3 in Hefei City, and propose effective measures.MethodsThe data of daily NAD, mortality due to circulatory system diseases, mortality due to respiratory system diseases, atmospheric pollution, and meteorological factors were collected in Hefei from 2017 to 2020. By fitting daily average temperature, relative humidity, time trend, and seasonal trend, a generalized additive model was applied to evaluate the single-day effects (lag0-lag5) and cumulative lag effects (lag01-lag05) of NAD, circulatory system mortality, and respiratory system mortality among residents of Hefei City for every 10 μg·m−3 increase in the daily maximum 8-hour average ozone (O3-8 h) concentration. The effects of O3-8 h concentration on total NAD were also examined by stratification of age and sex.ResultsDuring the period of 2017 to 2020, the average concentration of O3-8 h in Hefei City was 99.12 μg·m−3, and the total number of non-accidental deaths was 45787. For the O3-8 h concentration per 10 μg·m−3 increase, the single-day effect and cumulative lag effect on NAD among residents reached their maximum values at lag0 and lag02, respectively, with the NAD increasing by 0.46% (95%CI: 0.06%, 0.87%) and 0.76% (95%CI: 0.27%, 1.26%); the maximum estimates for deaths from circulatory diseases appeared on lag03 increasing by 0.78% (95%CI: 0.08%, 1.48%). The stratified analyses results showed that the single-day effects on the NAD in males and females reached the maximum values on lag1 and lag0, increasing by 0.64% (95%CI: 0.21%, 1.08%) and 0.61% (95%CI: 0.03%, 1.20%), respectively; on lag02, the NAD among males was the highest, reaching 0.98% (95% CI: 0.39%, 1.57%); significant estimates for NAD among residents aged 65 years and above were observed on lag1 and lag02 rising by 0.41% (95%CI: 0.02%, 0.81%) and 0.67% (95%CI: 0.13%, 1.21%), respectively. After adjusting the degrees of freedom of time trend and other atmospheric pollutants, there was no statistically significant change in the risk of NAD death among residents associated with O3-8h concentration.ConclusionThe increase O3 concentration in Hefei is correlated with an increased NAD risk among residents, with males and people over 65 years old having a higher risk of death due to O3 exposure. It is necessary for the government to play an important role in developing prevention and control measures to reduce the excess risk of death associated with O3 exposure.